Pengaruh Self-Awareness dan Self-Image dalam Meningkatkan Kepercayaan Diri Mahasiswa Keperawatan (D3) - Ruben Letlora; Nur Anisah; Ignatius Djuniarto (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Self-confidence is a person's basic asset in fulfilling various self- interests. With self-confidence, students are more daring to express their opinions in public and later will be able to carry out their roles and functions as nurses when working. Self-confidence can be increased by a positive self-awareness and self- image. To determine the effect of self awareness and self image in increasing self- confidence of D3 Nursing students of STIKES Wira Husada Yogyakarta. This research is a quantitative research with the type of pre-experimental with a one-group pretest-posttest design approach. The population in this study were D3 Nursing students at STIKES Wira Husada Yogyakarta batch 2019, 2020 and 2021. The sample of this study consisted of 30 students from the 2019 and 2021 classes. The research instrument used was the self awareness, MBSRQ-AS proposed by Seawell and Burg and a self-confidence questionnaire that has been tested for validity and reliability. The results of the research conducted showed that there were differences before and after self-awareness and self-image intervention by cognitive behavior therapy (CBT), namely before being given CBT therapy 14 students had negative self- confidence (46.7%) and 16 students had positive self-confidence ( 53.3%). After being given CBT therapy there was an increase in self-confidence, as many as 27 students had positive self-confidence (90.0%) and students who had negative self-confidence decreased to 3 students (10.0%). There is an effect of self-awareness and self-image in improving Self Confidence of D3 Nursing Students STIKES Wira Husada Yogyakarta. Keywords: Self Awareness, Self image, Self-confidence, Students, Cognitive Behavior Therapy (CBT) ABSTRAK Kepercayaan diri merupakan aset dasar seseorang dalam memenuhi berbagai kepentingan sendiri. Dengan rasa percaya diri mahasiswa lebih berani mengungkapkan pendapat didepan umum dan nantinya akan mampu menjalani peran dan fungsi sebagai perawat ketika bekerja. Kepercayaan diri dapat ditingkatkan dengan self awareness dan self image yang positif. Tujuan penelitian untuk mengetahui pengaruh self awareness dan self image dalam meningkatkan kepercayaan diri mahasiswa D3 Keperawatan STIKES Wira Husada Yogyakarta Metode: Penelitian ini merupakan penelitian kuantiatif dengan jenis penelitian pre eksperimen dengan pendekatan one-group pretest-posttest design. Populasi dalam penelitian ini adalah mahasiswa D3 Keperawatan di STIKES Wira Husada Yogyakarta angkatan 2019, 2020 dan 2021. Sampel penelitian ini berjumlah 30 mahasiswa Angkatan 2019 dan 2021. Instrument penelitian yang digunakan adalah kuesioner kuesioner self awareness, MBSRQ-AS yang dikemukakan oleh Seawell dan Burg dan kuesioner kepercayaan diri yang telah dilakukan uji kesahihan dan keandalan. Hasil penelitian yang dilakukan menunjukan bahwa terdapat perbedaan sebelum dan sesudah self awareness dan self image diintervensi cognitive behavior therapy (CBT) yaitu sebelum diberikan terapi CBT, 53,3% mahasiswa memiliki kepercayaan diri negatif dan 46,7% mahasiswa memiliki kepercayaan diri positif. Setelah diberikan terapi CBT mengalami peningkatan kepercayaan diri, sebanyak 90,0% mahasiswa memiliki kepercayaan diri positif dan mahasiswa yang memiliki kepercayaan diri negatif berkurang menjadi 10,0%. Ada pengaruh self awareness dan self image dalam meningkatkan Kepercayaan Diri Mahasiswa D3 Keperawatan STIKES Wira Husada Yogyakarta. Kata Kunci: Self awareness, Self image, Kepercayaan diri, Mahasiswa, Cognitive       Behavior Therapy (CBT).